The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3892/br.2016.717
|View full text |Cite
|
Sign up to set email alerts
|

Association of C677T MTHFR and G20210A FII prothrombin polymorphisms with susceptibility to myocardial infarction

Abstract: Abstract. Myocardial infarction (MI) is a common complex pathology, localized in the main leading causes of mortality worldwide. It is the result of the interaction of genetic and environmental factors. The aim of the present study was to investigate the potential association of C677T 5,10-methylenetetrahydrofolate reductase (MTHFR) (rs1801133) and G20210A factor II prothrombin (FII) (rs1799963) polymorphisms with the susceptibility of MI. Following extraction by the standard salting-out procedure, DNA samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 51 publications
0
3
0
3
Order By: Relevance
“…If the above polymorphism is combined with casual smoking, the risk is increased 22-fold (95% CI: 9.192-66.517) 71 . Hmimech et al showed that polymorphisms G20210A of prothrombin [FII] gene -even if there is a single or double copy of the 20210A allele-is highly associated with premature MI 73 .…”
Section: C) Homocysteinementioning
confidence: 99%
“…If the above polymorphism is combined with casual smoking, the risk is increased 22-fold (95% CI: 9.192-66.517) 71 . Hmimech et al showed that polymorphisms G20210A of prothrombin [FII] gene -even if there is a single or double copy of the 20210A allele-is highly associated with premature MI 73 .…”
Section: C) Homocysteinementioning
confidence: 99%
“…The remaining 143 manuscripts were screened and assessed based on the full text for eligibility. Eventually, 66 studies for C677T and 18 studies for A1298C qualified for quantitative analysis [21] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , ...…”
Section: Resultsmentioning
confidence: 99%
“…Нарушение фолатного цикла способствует гипергомоцистеинемии, что может приводить к гиперкоагуляции и формированию тромботических масс на сердечных клапанах [20,21]. Ген MTR кодирует аминокислотную последовательность фермента метионинсинтазы -одного из ключевых ферментов обмена метионина, катализирующего образование метионина из гомоцистеина путем его реметилирования.…”
Section: Discussionunclassified